2010
DOI: 10.1007/s00381-010-1164-4
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic enlarged Virchow–Robin spaces in a 6-year-old boy: a case-based update

Abstract: In this paper, we discuss the phenomenon of perivascular (Virchow-Robin) spaces and their treatment options and review the relevant literature. To our knowledge, this is the first pediatric case of tumefactive dilatation of the Virchow-Robin spaces causing obstructive hydrocephalus that were directly fenestrated using neuroendoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 17 publications
1
49
0
2
Order By: Relevance
“…37 Enlarged VRS can develop along the cingulate gyrus. 38 As in the present study, the majority of structural brain changes reported in HIV infection are localized to subcortical gray matter structures and white matter, adjacent to VRS. Previously we found that detectable PBMC HIV DNA was related to gray matter loss in the bilateral insula, cingulate cortex, and ventromedial prefrontal cortex near the optic tract.…”
supporting
confidence: 72%
“…37 Enlarged VRS can develop along the cingulate gyrus. 38 As in the present study, the majority of structural brain changes reported in HIV infection are localized to subcortical gray matter structures and white matter, adjacent to VRS. Previously we found that detectable PBMC HIV DNA was related to gray matter loss in the bilateral insula, cingulate cortex, and ventromedial prefrontal cortex near the optic tract.…”
supporting
confidence: 72%
“…Rarely, the VRS may reach giant sizes and cause a mass effect that may be misdiagnosed as a neoplasm [21]. Fayeye et al reported a 6-year-old boy with hydrocephalus and third nerve malfunction due to enlarged VRS [6]. [4].…”
Section: Discussionmentioning
confidence: 99%
“…Virchow-Robin spaces (VRS) are perivascular, pial-lined areas in the brain that surrounds small arteries and can be seen on brain magnetic resonance imaging (MRI) [6,9]. On MRI sequences, VRS are fluid-filled spaces, and their signal intensities are identical to those of cerebrospinal fluid [4,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4b), and the patient's signs and symptoms regressed, except for the oculomotor deficit. authors: expanding lacunae [7,9,10], expanding Virchow-Robin spaces [11], benign expanding cerebral cysts [7], giant dilations of perivascular spaces [3,5,12] or enlarged perivascular spaces [4,13], and oddly enough, virchomas [5]. Some of the names clearly recall the possible pathogenesis of these cystic lesions, considered by most authors to be merely an excessive dilation of Virchow-Robin physiological perivascular spaces (PVSs), which can be found anywhere in the brain [14].…”
Section: Casementioning
confidence: 99%